Adaptasi dan Ketahanan UMKM di Masa Pandemi Covid-19: Studi Empiris di Kota Kendari - Muh. Yani Balaka; La Karimuna; Gamsir Gamsir; Hasddin Hasddin; Taufik Taufik; Mirad Mirad; Alfian Ishak (Bomba: Jurnal Pembangunan Daerah, 2025)
The Covid-19 pandemic has created a wave of uncertainty that has led to economic failure and disruption, particularly in the micro and small business sector. This study aims to analyze the impact of the pandemic on MSMEs, using a case study in Kendari City, Southeast Sulawesi. This study uses primary data collected from 100 MSMEs in Kendari City through structured questionnaires and in-depth interviews, using a stratified random sampling method. The variables analyzed included income, number of employees, turnover, business capital, and marketing strategies before and after the COVID-19 pandemic. Data analysis was conducted using independent t-tests and fixed effects estimation to identify the impact of the pandemic on MSME performance and strategies. The analysis shows that the pandemic crisis has significantly impacted the economic system, particularly micro, small, and medium enterprises, as reflected in decreased income and disrupted employment, which in turn has led to increased unemployment. This impact has also affected business turnover and prompted changes in marketing strategies. Nearly 60% of MSMEs in Kendari City have experienced economic difficulties since the pandemic emerged in Indonesia. In Southeast Sulawesi, the decline in MSME performance is predicted to be primarily due to the low utilization of technology in product marketing, which is limited by the availability of funds.